Evaluasi Pemenuhan Standar Minimal Sarana dan Prasarana Pendidikan Dasar di Kota Bandung - Busono, Tjahyani (INVOTEC, 2011)
This research was aimed to describe the condition of infrastructure facilitiesof basic education based on the standard of school facilities and infrastructure/public madrasah (Permendiknas no. 24 2007). The results illustrate that the vast majority of school buildingsare in accordance with the standards established. Classrooms a splaces of teaching and learning in most primary schools have been very adequate. Only still found some schools that do not have the staff room, principal room, UKS space, prayer room, and werehouse representative in order to support teaching and learning activities. But still there are schools that less attention and support facilities not regularly carry out maintenance of the building. For schools that are in the main street, still unable to overcome the noise caused by traffic so that it can interfere with teaching and learning activities. The existence of the school adjacent to the crowd as the market also require attention to reduce the disruption of teaching and learning activities.